ANALISIS ASPEK KELAYAKAN USAHA PADA ERGO COFFE DI KABUPATEN JEMBER - Elasari Juniana; Heny Inayatul Maula; Hidayah Atta mimi; Rahmawati Rahmawati; Revi Septia (Faculty of Economics and Business University of Lampung, 2023)
Ergo Coffe is one of the cafes in Jember Regency with a main menu of coffee and non-coffee menus as well as light snacks whose prices are affordable for the pockets of the people, especially Jember. The purpose of this study was to analyze the feasibility of Ergo Coffee on legal aspects, technical and production aspects, market and marketing aspects, financial aspects, and environmental aspects. This research uses descriptive qualitative method. The research design used in this research is library research and field research. Collecting data in research using primary data, namely by interview. Ergo Coffe's financial aspect calculations obtained 515,000 in January and 515,600 in February.